Rekonstruksi Laporan Keuangan Masjid berdasarkan ISAK 35 Pada Masjid Nurul Iman Kota Putusibau: Rekonstruksi Laporan Keuangan Masjid berdasarkan ISAK 35 Pada Masjid Nurul Iman Kota Putusibau - Kurniati, Pratiwi; Sabirin, Sabirin; Anzil, Utin Rahmi (FAKULTAS EKONOMI DAN BISNIS ISLAM, 2020)
The mosque only presents simple financial reports such as infaq reports/mobile charity boxes which are usually reported once a week with financial reports so that it can assess the accountability of the board/management for the duties, obligations and performance mandated to them. The purpose of this study is to determine the preparation of the financial statements of the Nurul Iman Mosque and the reconstruction of the Financial Statements at the Nurul Iman Mosque based on the Interpretation of Financial Accounting Standards No. 35. The research used by researchers is a qualitative approach with field research. Data collection techniques namely by: Observation, Interview and Documentation. The data obtained is a financial report made by the Treasurer of the Nurul Iman Mosque which is then processed, analyzed, and conclusions are drawn. The results of this study are: (1) Nurul Iman Mosque has not implemented the preparation of financial reports in accordance with ISAK No. 35 and still use the preparation of financial reports with the recording of income and expenses which are recorded in the Friday cash book. (2) Components in the financial statements of the Nurul Iman Mosque which must be made in accordance with ISAK No. 35 which refers to 5 Components, namely Statement of Financial Position, Statement of Comprehensive Income, Report on Changes in Net Assets, Statement of Cash Flows, and Notes to Financial Statements.